2023
DOI: 10.3390/molecules28073164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anticancer Activity and Mechanism Studies of Glycyrrhetic Acid Derivatives toward HeLa Cells

Abstract: In this paper, a series of glycyrrhetic acid derivatives 3a–3f were synthesized via the esterification reaction. The cytotoxicity of these compounds against five tumor cells (SGC-7901, BEL-7402, A549, HeLa and B16) and normal LO2 cells was investigated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. The results showed that compound 3a exhibited high antiproliferative activity against HeLa cells (IC50 = 11.4 ± 0.2 μM). The anticancer activity was studied through apoptosis, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It has been reported that pentacyclic triterpenoid derivatives often inhibit the growth of cancer cells and are dependent on ROS activity [ 38 , 39 ]. However, their mechanism of action in the field of pesticides has rarely been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that pentacyclic triterpenoid derivatives often inhibit the growth of cancer cells and are dependent on ROS activity [ 38 , 39 ]. However, their mechanism of action in the field of pesticides has rarely been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In NSCLC cells, FOCAD inhibited FAK activity, enhancing sensitivity to ferroptosis [ 53 ]. Additionally, inhibition of FAK activity in ovarian [ 54 , 55 ] and cervical cancers [ 56 ] led to decreased GSH levels. FAK also serves as a scaffold for the binding of p53 and Mdm2, regulating ferroptosis via p53 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, identified compounds in HPLC-MS analysis have exhibited properties that benefit skin health, such as antimicrobial, antioxidant, anti-inflammatory, chemoprotective, cytotoxic, and wound-healing properties [ 49 , 50 , 51 , 52 ]. Therefore, these compounds may be responsible for the observed biological activities.…”
Section: Discussionmentioning
confidence: 99%